2016
DOI: 10.15517/am.v28i1.21903
|View full text |Cite
|
Sign up to set email alerts
|

Respuestas al estrés por calor en los cultivos. I. Aspectos moleculares, bioquímicos y siológicos.

Abstract: RESUMENEl objetivo de esta revisión fue integrar los mecanismos por los cuales las plantas responden al estrés por calor a lo largo del continuo suelo-planta-atmósfera, desde una perspectiva agronómica. Esta revisión presenta las bases fisiológicas del estrés por calor, para lo cual se examinaron las temperaturas óptimas y los umbrales de estrés por calor en los cultivos, las metodologías para su estudio, y las respuestas moleculares, bioquímicas y fisiológicas de las plantas a altas temperaturas. Se describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 100 publications
0
8
0
3
Order By: Relevance
“…The consumption of these compounds has been proposed as a method of protection against diseases (Yu et al, 2016), and may act as exogenous agents capable of protecting the cell from oxidative damage (Hostetler et al, 2017), However, their synthesis may be influenced by abiotic stress, corresponding to environmental factors such as temperature, humidity and/or ultraviolet radiation, to which the bush is subjected during its growth (Liu et al, 2017;Khoo et al, 2017). Studies on plant food sources have shown that exposure to different abiotic stressors increase anthocyanin concentrations (Li et al, 2018;Altangerel et al, 2017;Chavez-Barrantes & Gutiérrez-Soto, 2017), which may be due to the specific role that these compounds play in the plant during abiotic stress, such as ROS cooling, photoprotection, stress signaling and/or xenohormesis (Kovinich et al, 2015). The objective of this study was to compare the antioxidant capacity of Calafate collected at different locations in southern Chile, specifically Aysén and Magallanes.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of these compounds has been proposed as a method of protection against diseases (Yu et al, 2016), and may act as exogenous agents capable of protecting the cell from oxidative damage (Hostetler et al, 2017), However, their synthesis may be influenced by abiotic stress, corresponding to environmental factors such as temperature, humidity and/or ultraviolet radiation, to which the bush is subjected during its growth (Liu et al, 2017;Khoo et al, 2017). Studies on plant food sources have shown that exposure to different abiotic stressors increase anthocyanin concentrations (Li et al, 2018;Altangerel et al, 2017;Chavez-Barrantes & Gutiérrez-Soto, 2017), which may be due to the specific role that these compounds play in the plant during abiotic stress, such as ROS cooling, photoprotection, stress signaling and/or xenohormesis (Kovinich et al, 2015). The objective of this study was to compare the antioxidant capacity of Calafate collected at different locations in southern Chile, specifically Aysén and Magallanes.…”
Section: Introductionmentioning
confidence: 99%
“…When stomata are closed by stress induced by factors such as high radiation, heat or drought, the dissipation of radiation in the form of latent heat is reduced and the temperature of the leaf rises in a vicious circle [37]. If the stress is prolonged over time, the integrity of photosystem II is compromised due to the stacking of thylakoid membranes, thus reducing the photosynthetic efficiency [38].…”
Section: Discussionmentioning
confidence: 99%
“…Under stress conditions such as high temperature [30], waterlogging [31], salinity [32], and hydric and nutrient deficiencies [25], plants must change their physiology and increase their efficiency so as to use few nutrients available to fulfill their development cycles as occurs under O 0 .…”
Section: Discussionmentioning
confidence: 99%